Pengembangan Framework Pengukuran Kinerja Rantai Pasok Perikanan Budidaya Tambak - Widyaningrum, Dzakiyah; Ismiyah, Elly (Muhammadiyah University Press, 2019)
To succeed in global competition, the proper aquaculture fish farming supply chain must be built. To determine the accuracy of its supply chain, it is necessary to measure it with the right measuring instruments according to its characteristics. Modeling a conceptual framework for measuring the performance of aquaculture fish farming supply chain is carried out by involving stakeholders as respondents. Expert respondents are selected so that the framework is designed appropriately. A deep literature review, a deep discussion, and a questionnaire are used to identify its indicators and sub-indicators that are following the characteristics of a fishery aquaculture supply chain. These indicators and sub-indicators will be structured into a hierarchy, and then an analytical hierarchy process (AHP) will be investigated and rank the weight of indicators and sub-indicators. This paper concludes that this framework can be used to measure the performance of aquaculture fish farming supply chain. Its measurement result can help the stakeholders to prioritize supply chain improvements on important indicators with poor performance.